Legal Reconciliation in Resolving Social Conflicts Between the State and Indigenous Communities - Abdul Rochim; Mohamad Tohari; Naya Amin Zaini (Lembaga Pengembangan Kinerja Dosen, 2026)
In contemporary legal systems, social conflict between the state and indigenous communities is a complicated matter, especially when it comes to the acknowledgement and defense of indigenous peoples' rights to land, natural resources, and cultural identity. Indigenous peoples' rights, which before the establishment of the modern state, are frequently disregarded by imbalances in official policies that prioritize development interests. In this context, legal reconciliation is a relevant approach to resolving these conflicts in a just and sustainable manner. Legal reconciliation emphasizes the integration of customary law into the national legal system and the harmonization of state policies and the interests of indigenous peoples to create a more inclusive legal order. The study of legal standards relevant to resolving disputes between the state and indigenous peoples is the main emphasis of this research, which employs a normative juridical approach. The approach used in this research includes an analysis of national legislation, international legal instruments related to indigenous peoples' rights, and relevant legal doctrines. Using a statute approach and a conceptual approach, this research explores how legal reconciliation can be implemented in resolving social conflicts. Furthermore, this research highlights the role of legal principles such as restorative justice, legal pluralism, and recognition of indigenous peoples' rights in developing more effective conflict resolution mechanisms. This analysis is expected to establish a strong legal foundation for promoting more inclusive and socially just legal policies for indigenous peoples.